Kualitas Air dan Indeks Pencemaran pada Sungai Arbes Desa Batu Merah Kota Ambon - Gea, Liyatin; Muhamad Hariono; Lolita Tuhumena; Imam Misbach; Kristina Haryati (Cenderawasih University, 2024)
Uncontrolled use of the Arbes river due to human activities causes pollution, thereby causing a decline in river water quality. This research aims to determine the quality of river water in terms of physical, chemical and biological factors in the Arbes River.This research was conducted from January to February 2019by taking Arbes River water samples using the quadratic linear transect method.The research sampling transect line measurements were carried out horizontally, namely from upstream to downstream of the river.Arbes River water quality analysis testing was carried out at the MIPA IAIN Ambon laboratory.The results of the analysis of the water quality of the Arbes River physically, chemically and biologically have decreased with the water quality criteria based on PP 82 of 2001 being classified as class II quality water which is not intended as a raw source of drinking water but is more suitable for washing and agriculture.Based on determining the Pollution Index (IP) value, the results of the pollution index for use (Pij) in Arbes river water are included in the lightly polluted category.The highest pollution index value for use (Pij) is found in the lower reaches of the river, namely 1.869. Meanwhile, the Pij value in the middle of the river is 1.784. And the lowest Pij value is found in the upper reaches of the river at 1.677.